PROFESIONALISME GURU MATEMATIKA DALAM MENGHADAPI PERKEMBANGAN TEKNOLOGI DIGITAL - Dina Arsita; Anisa Ramadani; Ikmawati; Achmad Muhtadin (CV. ADIBA AISHA AMIRA, 2026)
Advances in digital technology have transformed mathematics education and require teachers to enhance their professional competence to meet the demands of the digital age. Technology is no longer merely a tool but has become an integral part of learning, as it can present abstract mathematical concepts through visualization, simulation, and interactive media. However, the implementation of digital technology still faces various challenges, such as limited teacher competencies, low digital literacy, disparities in technology access, and suboptimal pedagogical practices. This study employs a literature review method using national journal articles (2016–2025) with thematic synthesis analysis to identify relevant patterns and relationships. The results indicate that teacher professionalism focuses not only on subject matter mastery but also on the ability to integrate knowledge, content, and pedagogical technology (PCK and TPACK). Appropriate technology integration has been proven to enhance learning quality, student engagement, and conceptual understanding. However, the optimal use of technology still needs improvement. Therefore, teacher professionalism must be continuously developed, particularly in the areas of pedagogy, digital literacy, and technology integration, to create effective, innovative, and meaningful mathematics learning.